Drying kinetics and change in bioactive compounds of edible flowers: Prunus domestica - Dundar, Ayse Neslihan; Sahin, Oya Irmak; Parlak, Mahmut Ekrem; Saricaoglu, Furkan Turker (Wiley, 2023)
The aim of the study is to reveal the effect of different drying methods (hot-air drying [HAD] and freeze-drying [FD]) on flowers of Prunus domestica-white, pink, and red, methanolic extracts and their effects on polyphenolic compounds. Drying kinetics, phytochemical and antioxidant activity were investigated, and compared with each other and also with fresh samples. The modeling of the terms of Fick's diffusion equation were used to estimate the coefficients of diffusion. Drying kinetics from HAD and FD were analyzed mathematically, and obtained data was statistically analyzed to obtain best fit among all available models. The total phenolic content (TPC) of plum blossom extracts (PBEs) varied between 185.16 and 279.73 mg GAE per g dry weight sample. TPC levels increased in red and white PBE samples subjected to the FD process. However, in contrast, the TPC values of the pink PBE were in a decreasing trend with the drying process. CUPRAC levels were highest in the PBE of red flowers (1.04 mmol TE g(-1)). ABTS (65 mu mol TE g(-1)) and DPPH (47.50 mu mol TE g(-1)) levels were highest in PBE of pink flowers. ABTS values of only red-colored samples increased after HAD and FD, while antioxidant activity results decreased in all other samples. Compared to HAD, FD negatively affected quercetin and its derivative content, on the other hand positively affected the cyanidin contents. It can be concluded that different drying methods would be effective for different polyphenolic compounds depending on the pigment type of flowers. Practical applications Edible flowers have been used for their therapeutic purposes traditionally, and nowadays they gain a renewed interest as rich sources of bioactive compounds for both the food and culinary science. As a new tool for functional food development, the focus of edible flowers research is how to preserve the bioactive content. Drying is known to be the best way to avoid the perishability of edible flowers. The present work has been carried out for comparing two drying methods (HAD, FD) in terms of the bioactive changes and kinetic parameters. Our results showed that the quality attributes of Prunus flowers, rich in bioactive compounds and pigments, either preserve or enhance by FD. Mathematical modeling of drying affected by the pigment types, which is determined Jena&Das model for white flowers while Page model was the most appropriate to describe drying kinetics of red and pink flowers. It can be concluded that freeze drying can be effectively used in the dehydration of Prunus flowers and further studies can be promoted as a functional additive.
Keywords: antioxidant activity; drying; drying kinetics; edible flower; phenolic compounds; Prunus domestica